Analisis Respon Pemanfaatan Teknologi, Informasi, dan Komunikasi pada Media Live Worksheet terhadap Pelajaran PAI di Sekolah - Mulyati, Yanti (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
This research is motivated by the assumption that developments in technology, information and communication can encourage positive changes in the field of education. Moreover, technology, information, and communication can also encourage the development of electronic-based learning concepts. The purpose of the research is to analyze and describe the students' responses to the use of technology, information, and communication assisted by live worksheet media on learning outcomes in PAI lessons at school. This research design is exploratory and using descriptive method. The data collection technique uses a questionnaire in the form of statements. The data analysis technique uses a quantitative approach. The results of the research show that the average student response is 77% in the good category. An important finding of the research is the use of technology, information, and communication through Live Worksheet media has proven to be able to be used as an alternative for fun learning. The implication of the research is every student needs to be given the same opportunity to develop in the learning process and it is also needed to be more comprehensive study to examine the student’s responses to learning through using liveworksheet media in PAI learning at school.